Analisis Penganggaran Modal pada Usaha Mikro Kecil dan Menengah (UMKM) di Kabupaten Bandung Barat - Debbie Christine; Apriwandi; Andina Nur Fathonah; Erly Sherlita; Aida Wijaya; Eriana Kartadjumena (Jurnal EMT KITA, 2023)
This study aims to analyze the practice of capital budgeting in Micro, Small and Medium Enterprises (MSMEs) in West Bandung Regency. This research was conducted because in carrying out their activities, MSME actors often experience limited capital. Therefore, it is necessary to make the right project decision. Capital budgeting is seen as an important thing done by business actors in making project decisions. This study adopts an exploratory and qualitative approach in measuring capital budgeting practices in MSMEs. Data collection techniques used observation, interviews and documentation. The results show that the practice of capital budgeting decisions is not fully applicable to MSMEs. This can be seen from project activities, planning activities and methods of assessing capital budgeting for SMEs.